Terapi Realitas untuk Meningkatkan Self Esteem pada Wanita di Panti Sosial - Dhira Airin Aulia; Rilla Sovitriana (Jurnal Ilmiah Psikologi MIND SET, 2021)
Panti Sosial Wanita is one of the implementing units (UPT) within the Ministry of Social Affairs of the Republic of Indonesia which is given the task to provide services and rehabilitation for beneficiaries. Based on the results of field observations and interviews with beneficiaries at the Social Home for Women in Jakarta, it is known that many beneficiaries who have difficulty in following coaching programs such as decreased self esteem are marked by solitary behavior, shyness, easy to give up, pessimistic, passive and unstable emotions. The subjects of this study were beneficiaries in women's social homes as many as 5 people. The purpose of this study is to find out the picture of self esteem in Beneficiaries in Women's Social Homes and get the results of the application of Reality therapy with WDEP techniques to increase self esteem in Beneficiaries in Women's Social Homes Jakarta, this form of therapy is carried out systematically for 10 sessions. This study uses quasi-experimental data analysis techniques using pattern matching and analysis of developmental results. Self esteem measurement results using Rosenberg Self Esteem Scale (RSES) in the form of pre-test and post-test. Pre-test results showed an average score of 14 groups with low self esteem categories. Based on the results of the application of reality therapy with WDEP techniques the subjects showed behavior willing to socialize, not shy, unyielding, optimistic, active and stable emotions. These results are supported by post-test results using the RSES scale with an average score of 29 groups in the moderate self esteem category.